Correlation Between Intimate Partner Violence Victimization and Risk of Substance Abuse and Depression among African-American Women Seen in an Urban Emergency Department - Houry, Debra; Daugherty, Jill; Smith, L. Shakiyla; Hankin, Abigail (Western Journal of Emergency Medicine, 2010)
Objective: To assess rates of substance abuse (including tobacco, alcohol, and drug abuse) as well as rates of intimate partner violence (IPV) among African-American women seen in an urban Emergency Department (ED). Methods: Eligible participants included all African-American women between the ages of 21-55 years old who were seen in an urban ED for any complaint, and who were triaged to the waiting room. Eligible women who consented to participate were taken to complete a computer-based survey that focused on demographic information and general health questions as well as standardized instruments including the Index of Spouse Abuse (ISA), the Tolerance, Worried, Eye openers, Amnesia, K(C)ut down (TWEAK) screen for alcohol abuse, Drug Abuse Screening Test (DAST20), and Hooked on Nicotine Checklist (HONC). This analysis uses results from a larger study evaluating the effects of providing patients with targeted educational literature based on the results of their screening. Results: 610 women were surveyed. Among these, 85 women (13.9%) screened positive for IPV. Women who screened positive for IPV were significantly more likely to also screen positive for tobacco abuse (56% vs. 37.5%, p< 0.001), alcohol abuse (47.1% vs. 23.2%, p < 0.001), and drug abuse (44.7% vs. 9.5%, p<0.001). Women who screened positive for IPV were also more likely to screen positive for depression and to report social isolation. Conclusion: African-American women seen in the ED, who screen positive for IPV, are at significantly higher risk of drug, alcohol, tobacco abuse, depression and social isolation than women who do not screen positive for IPV. These findings have important implications for ED-based and community-based social services for women who are victims of intimate partner violence. [West J Emerg Med. 2010; 11(3): 253-257.]